2020
DOI: 10.3390/cancers12071857
|View full text |Cite
|
Sign up to set email alerts
|

Metformin and Probiotics in the Crosstalk between Colitis-Associated Colorectal Cancer and Diabetes in Mice

Abstract: The co-occurrence of colorectal cancer (CRC) and diabetes mellitus along with inflammation and dismicrobism has been frequently reported. Several studies shed light on the antioncogenic potential of metformin on colorectal carcinogenesis. This study aimed to demonstrate that metformin in association with probiotics acts in a synergic effect in breaking the crosstalk, thus inhibiting CRC progression, improving diabetes, and reducing inflammation. Ninety-six male Balb/c mice, 6–8 weeks old, were divided … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 63 publications
0
16
0
Order By: Relevance
“…improved glucose homeostasis, suggestive of better efficacy of Met via gut modulation [10]. Various reports suggesting the beneficial effects of combination therapy with probiotic and Met in many diseases including diabetes mellitus, colorectal cancer, and nonalcoholic steatohepatitis (NASH) exist [12,19,20], but there have been narrow efforts to evaluate the possible benefits of the combined administration of probiotics and Met in ethanol-induced hepatic injury. Based on the above studies as well as the individual protective role of probiotics and Met towards alcoholic liver injury, the current study evaluated the combined effect of probiotic V and Met in modulating ethanol-induced hepatic injury using in vitro and in vivo models.…”
Section: Introductionmentioning
confidence: 99%
“…improved glucose homeostasis, suggestive of better efficacy of Met via gut modulation [10]. Various reports suggesting the beneficial effects of combination therapy with probiotic and Met in many diseases including diabetes mellitus, colorectal cancer, and nonalcoholic steatohepatitis (NASH) exist [12,19,20], but there have been narrow efforts to evaluate the possible benefits of the combined administration of probiotics and Met in ethanol-induced hepatic injury. Based on the above studies as well as the individual protective role of probiotics and Met towards alcoholic liver injury, the current study evaluated the combined effect of probiotic V and Met in modulating ethanol-induced hepatic injury using in vitro and in vivo models.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study of diabetic and non-diabetic mice with induced colorectal cancer showed that metformin treatment in association with probiotics containing Bifidobacterium species actively prevented inflammatory and carcinogenic processes [ 34 ]. Furthermore a study of H. pylori -related gastric lesions showed a higher relative abundance of Firmicute in gastritis and gastric metaplasia patients [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…In diabetic patients, metformin reduced the incidence of adenomas that could transform into colorectal cancer; therefore, metformin may be useful for the prevention of colorectal cancer in patients with type 2 diabetes [ 45 ]. In mice, metformin use in association with probiotics reinforces beneficial effect on colorectal cancer prevention [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Immunohistochemistry for CYP4A (1:150, Abcam, Cambridge, MA 02139, USA) was done on paraffin-embedded tissue sections as previously described [ 76 ]. Sections were examined under the light microscope (Olympus CX41 for slide imaging), and analysis of the sections was performed using Image J software version 1.53.…”
Section: Methodsmentioning
confidence: 99%
“…The pathogenesis of fibrosis and inflammation due to iron overload and increase in ROS production was shown by H&E and Masson trichrome staining as previously described [ 76 ].…”
Section: Methodsmentioning
confidence: 99%